(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research Reviews the sides of highlight importance of the Nano-Accounting which doing the accounting performance functions fully computerized without the intervention of an accountant, to solve the problem of not keeping up the rationalization of recording and accounting systems, with the rationalization of production which fully computerized.(be invisible and hidden accounting), resulting by linking or interaction of the accounting, additive production system represented three-dimensional printers, open source and recycling. That which result the rationalizing the facilities of production, organization and self-control which derived nanotechnology idea, which aims to minimize materials and change it properties, then view the advantages , and the mechanism of Nano-accounting and the basic pillars upon which, the rationalized sides of accounting performance which traditionally played by the accountant as traditional accounting cycle as recording journal entries, posting ,balancing ,etc. which required changing the concept of accounting records to accounting notation, working on the development of the accounting from existing the accounting records to a good decisions maker, rationalize the principles and concepts of most the accounting and managerial systems as a result of changing the accounting structure, and removing jamming informatics.by direct contact for all internal and external parties, can illustrate the applications of Nano-Accounting by rationalized accounting performance in the manufacturing as a society of the research, and at the General Company for Electrical Industries / air cooler motor plant as a sample of the search.